Healer-led vs. clinician-led training to improve personal protective equipment use among traditional healers in South Africa: a randomized controlled trial protocol. Issue 1 (1st January 2021) - Audet, Carolyn M.; Shepherd, Bryan E.; Aliyu, Muktar H.; Moshabela, Mosa; Pettapiece-Phillips, Mariah J.; Wagner, Ryan G.
ABSTRACT: There are estimated two million traditional healers in sub-Saharan Africa (SSA), with more than 10% (200, 000) working in South Africa. Traditional healers in SSA are frequently exposed to bloodborne pathogens through the widespread practice of traditional 'injections', in which the healers perform dozens of subcutaneous incisions to rub herbs directly into the bloodied tissue with their hands. Healers who report exposure to patient blood have a 2.2-fold higher risk of being HIV-positive than those who do not report exposure. We propose a randomized controlled trial (61 healers in the intervention group and 61 healers in the control group) in Mpumalanga Province. Healers will receive personal protective equipment (PPE) education and training, general HIV prevention education, and three educational outreach visits at the healer's place of practice to provide advice and support for PPE use and disposal. Healers in the control arm will be trained by health care providers, while participants in the intervention arm will receive training and outreach from a team of healers who were early adopters of PPE. We will evaluate intervention implementation using data from surveys, observation, and educational assessments. Implementation outcomes of interest include acceptability and feasibility of PPE use during clinical encounters and fidelity of PPE use during treatments that involve blood exposure. We will test our two intervention strategies to identify an optimal strategy for PPE education in a region with high HIV prevalence.